Solubility Enhancement Methods Of Efavirenz : A Review - febryanto, hery diar; Eryani, Mikhania Christiningtyas; Husni, Patihul (Universitas Padjadjaran (Unpad), 2024)
Human Immunodeficiency Virus (HIV) is a global public health concern due to its progression to acquired immunodeficiency syndrome (AIDS) and the associated high morbidity and mortality rates. Efavirenz (EFV), an antiretroviral drug, is widely used to manage HIV/AIDS. However, EFV exhibits poor aqueous solubility and variable bioavailability, necessitating techniques to enhance its solubility and dissolution for improved therapeutic efficacy. This study reviewed methods to enhance EFV solubility using data from research published between 2019 and 2023. Various approaches, including Nano Micelles, Wet Milling, Co-crystals, Physical Mixtures, Nanocrystals, Dry Milling, and Liquisolid techniques, were analysed. The results demonstrated significant solubility enhancements. For instance, Fuentes (2024) achieved a 50% dissolution efficiency using Nano Micelles, while wet milling by Prado (2024) increased dissolution from 83.48% to 99.10% over 150 minutes. Co-crystals, such as those studied by Gowda (2022), improved solubility from 94.16 µg/mL (pure EFV) to 197.32 µg/mL (EFV-DL-Alanine). Sartori's (2022) Nanocrystals technique demonstrated a dissolution efficiency of 98.41%. Furthermore, physical mixtures like Nel's (2022) combination of EFV with pea protein isolate achieved a solubility increase from 1.00 mg/mL to 2.30 mg/mL. These methods highlight advancements in solubility enhancement techniques that improve EFV’s pharmacokinetic profile. These findings can guide the development of more effective pharmaceutical formulations, improving treatment outcomes for individuals living with HIV/AIDS.